(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
Corporate transparency has become an increasingly important factor in shaping investor confidence and market credibility, particularly in economies undergoing institutional transformation. In Uzbekistan, ongoing governance reforms have drawn attention to the role of corporate boards in ensuring effective disclosure practices and accountability. This article examines how board effectiveness influences corporate disclosure quality in Uzbek companies. The analysis focuses on board composition, oversight functions, decision-making processes, and their connection to transparency in financial and non-financial reporting. The study argues that ineffective boards often contribute to limited or inconsistent disclosure, which increases information asymmetry and perceived investment risk. Conversely, companies with more active and independent boards tend to demonstrate higher disclosure standards and greater transparency. The findings suggest that strengthening board effectiveness is a key element in improving corporate disclosure practices and supporting broader governance reform efforts in Uzbekistan.